A Convolution Approach on Partial Sums of Certain Harmonic Univalent Functions. (11th November 2012) - Porwal, Saurabh
Abstract : The purpose of the present paper is to establish some new results giving the sharp bounds of the real parts of ratios of harmonic univalent functions to their sequences of partial sums by using convolution. Relevant connections of the results presented here with various known results are briefly indicated.